Identifying Elective Induction of Labor among a Diverse Pregnant Population from Electronic Health Records within a Large Integrated Health Care System - Xie, Fagen; Fassett, Michael J.; Im, Theresa M.; Park, Daniella; Chiu, Vicki Y.; Getahun, Darios (American Journal of Perinatology, 2024)
Objective Distinguishing between medically indicated induction of labor (iIOL) and elective induction of labor (eIOL) is a daunting process for researchers. We aimed to develop a Natural Language Processing (NLP) algorithm to identify eIOLs from electronic health records (EHRs) within a large integrated health care system.Study Design We used structured and unstructured data from Kaiser Permanente Southern California's EHRs of patients who were <35 years old and had singleton deliveries between 37 and 40 gestational weeks. Induction of labor (IOL) pregnancies were identified if there was evidence of an IOL diagnosis code, procedure code, or documentation in a delivery flowsheet or progress note. A comprehensive NLP algorithm was developed and refined through an iterative process of chart reviews and adjudications, where IOL-associated reasons (medically indicated vs. elective induction) were reviewed. The final algorithm was applied to discern the indications of IOLs performed during the study period.Results A total of 332,163 eligible pregnancies were identified between January 1, 2008, and December 31, 2022. Of these eligible pregnancies, 68,541 (20.6%) were IOL, of which 6,824 (10.0%) were eIOL. Validation of the NLP process against 300 randomly selected pregnancies (100 eIOL, iIOL, and non-IOL cases each) yielded a positive predictive value of 83.0% and 88.0% for eIOL and iIOL, respectively. The rates of eIOL among the maternal age groups ranged between 9.6 and 10.3%, except for the <20 years group (12.2%). Non-Hispanic White individuals had the highest rate of eIOL (13.2%), while non-Hispanic Asian/Pacific Islanders had the lowest rate of eIOL (7.8%). The rate of eIOL increased from 1.0% in the 37-week gestational age (GA) group to 20.6% in the 40-week GA group.Conclusion Findings suggest that the developed NLP algorithm effectively identifies eIOL. It can be utilized to support eIOL-related pharmacoepidemiological studies, fill in knowledge gaps, and provide content more relevant to researchers.Key Points
Keywords: pregnancy; induction of labor; elective induction of labor; electronic health record; natural language processing; algorithm